PSYCHOLOGICAL RESOURCES OF INDIVIDUALS IN THE CONTEXT OF ARMED CONFLICT: ANALYSIS OF THE RESULTS OF A COMPREHENSIVE EMPIRICAL STUDY - Андросович, Ксенія; Кузьменко, Галина (SWorldJournal, 2025)
The article presents the results of a comprehensive empirical study of psychological resources of individuals in conditions of armed conflict. The relevance of the topic is determined by profound social transformations and a high level of stress factors,